Effects of lithium insertion into vanadium pentoxide thin films. Continuum radiation study - K. Bria; M. Ait El Fqih; R. Jourdani; L. Jadoual; A. Kaddouri (Ядерна фізика та енергетика)
Optical emission of Lix(x=0.2,0.7,1.2)V2O5 has been studied during 5 keV Kr+ ions bombardment. Continuous luminescence was observed in a broad wavelength range between 280 and 340 nm. Generally, the emission intensity was influenced by the quantities of lithium giving rise to transient effects as well as an increase in the line intensity. The experimental results suggest that the continuum emission depends on the nature of surface interaction between lithium and vanadium pentoxide and is very probably related to its electronic structure.